2017
DOI: 10.1096/fj.201601200rr
|View full text |Cite
|
Sign up to set email alerts
|

Mannan‐binding lectin, a serum collectin, suppresses T‐cell proliferationviadirect interaction with cell surface calreticulin and inhibition of proximal T‐cell receptor signaling

Abstract: Mannan binding lectin (MBL), initially reported to activate the complement pathway, is also known to be involved in the pathogenesis of autoimmune diseases. We report a thus far unknown function of MBL as a suppressor of T-cell activation. MBL markedly inhibited T-cell proliferation induced by anti-CD3 and anti-CD28 antibodies. Moreover, the presence of MBL during T-cell priming interfered with proximal T-cell receptor signaling by decreasing phosphorylation of Lck, ZAP-70, and LAT. MBL bound to T cells throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 40 publications
4
51
1
Order By: Relevance
“…In the present study, we investigated the signaling pathway and found that the phosphorylations of JNK, ERK and p38 were all significantly increased in MBL –/– mice after APAP treatment, suggesting that MBL attenuates the hepatic activation of MAPKs pathway in the context of APAP overdosing. The result is consistent with our and others’ previous reports showing that MBL could significantly down‐regulate the phosphorylation of MAPKs in different cell types in response to various stimulation . Among the MAPKs, JNK acts as a central player in the pathophysiology of APAP‐induced liver injury .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we investigated the signaling pathway and found that the phosphorylations of JNK, ERK and p38 were all significantly increased in MBL –/– mice after APAP treatment, suggesting that MBL attenuates the hepatic activation of MAPKs pathway in the context of APAP overdosing. The result is consistent with our and others’ previous reports showing that MBL could significantly down‐regulate the phosphorylation of MAPKs in different cell types in response to various stimulation . Among the MAPKs, JNK acts as a central player in the pathophysiology of APAP‐induced liver injury .…”
Section: Discussionsupporting
confidence: 93%
“…41 In this study, we observed the colocalization of MBL and α-SMA + activated HSCs in the peri-tumor region of either mouse or human HCC, but the MBL expression was hardly detected in either mouse HSCs or human HSC line LX-2 cells. It is not surprising that MBL can bind to the surface of LX-2 cells given our recent study showing that MBL could bind to calreticulin on the T cell surface 15 and the calreticulin has been reported to be present on the LX-2 cell surface. 42 This finding also could be supported by the previous data demonstrated that complement components such as C5a and mannan binding lectinassociated serine protease 1 (MASP-1), as well as C1q/tumor necrosis factor related protein 3 (CTRP3) with a collagen domain and a globular C1q domain that was similar with MBL, could modulate the HSCs activation.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, our recently studies showed that MBL could exert its immunomodulatory function apart from complement activation. [12][13][14][15] Although most previous studies were focused on the contribution of MBL to infectious diseases and autoimmune diseases, 16 accumulating evidence suggests that MBL is also involved in development of several cancer types. 17 However, the effect of MBL on tumor development, especially its role in the TME remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the absence of MBL might protect from intracellular parasitism/infections, since MBL might favour infection with mycobacteria ( Mycobacterium tuberculosis and Mycobacterium leprae ) [111]. However, also the exact opposite has been hypothesized, by showing that coincubation of T cells with MBL inhibits T cell activation, while the absence of functional MBL has been implicated to promote T cell driven autoimmune processes such as systemic lupus erythematosus and rheumatoid arthritis [130].…”
Section: Collectinsmentioning
confidence: 99%